Major Royal Jelly Proteins promote C2C12 myotubes differentiation by improving mitochondrial function - Zhang, Xin; Wei, Jinting; Liao, Suchan; Huang, Lingling; Bai, Zhikun; Hu, Yue; Yang, Caiyan; Zhong, Bin; Gu, Yishen; Li, Biao; Wang, Jinhua (Frontiers in Nutrition, 2026)
Royal Jelly (RJ) has been widely used as a health-promoting supplement and its bioactive component is the Major Royal Jelly Proteins (MRJPs). Whether MRJPs promote skeletal-muscle-cell development remains unresolved. Muscle dysfunction is linked to mitochondrial depletion and protein breakdown. Thus, we evaluated how MRJPs affect myotube differentiation. Myotubes morphology and number were measured using fluorescence microscopy and Coomassie brilliant blue staining, and C2C12 myotube differentiation was assessed using Western blotting or qRT-PCR analysis of the expression of MyoD, MyoG, Myosin Heavy Chain (MyHC) and muscle ring finger 1 (MuRF-1). Mitochondrial function was assessed with fluorescent probes, whereas the content of mitochondria was determined by analyzing the expression of related proteins. Western blotting was used to examine the expression of myosin-associated proteins, autophagy-associated proteins, apoptosis-associated proteins, and mitochondria-associated proteins. This was demonstrated by increased myotubes density and length, and increased mRNA and proteins expression of MyoD, MyoG and MyHC. In this study, we found that MRJPs promoted the differentiation of C2C12 myoblasts to form myotubes, but could not reverse Dex-induced muscle atrophy. The possible mechanism is that MRJPs reduced apoptosis increased cellular autophagy, stimulated mitochondrial biogenesis, promoted mitochondrial dynamics homeostasis and mitophagy, and prevented the loss of mitochondrial membrane potential.